3.27. Dany jest wzór funkcji kwadratowej y = a * (x – p) ^ 2 + q , a ne0 stawie wartości a i q, liczbę miejsc zerowych tej funkcji. a) y = 3 * (x – 1) ^ 2 + 4 d) y = 1/4 * (x – 4) ^ 2 + 1 b) y = – 1/2 * (x + 3) ^ 2 + 5 e) y = – (x + 5) ^ 2 . Podaj, na pod c) y = (x + 8) ^ 2 – 2 f) y = – 2 * (x + 1) ^ 2 – 6

3.27. Dany jest wzór funkcji kwadratowej y = a * (x – p) ^ 2 + q , a ne0 stawie wartości a i q, liczbę miejsc zerowych tej funkcji. a) y = 3 * (x – 1) ^ 2 + 4 d) y = 1/4 * (x – 4) ^ 2 + 1 b) y = – 1/2 * (x + 3) ^ 2 + 5 e) y = – (x + 5) ^ 2 . Podaj, na pod c) y = (x + 8) ^ 2 – 2 f) y = – 2 * (x + 1) ^ 2 – 6